Analysis of factors related to student academic procrastination - Fridayani, Januari Ayu (The International Journal of Business Review (The Jobs Review), 2023)
Academic procrastination, if left unchecked and unmanaged, will have an impact on reducing student productivity and fatally have a negative impact on their future. This research focuses on three aspects that can be personally managed by students and are seen as having a relationship to academic procrastination, namely self-efficacy, time management, and self-motivation. The sample used in this study was 150 students from the Faculty of Economics, University of Sanata Dharma, using the quantitative method and the SPSS version 25 test tool. The data were obtained by distributing questionnaires, which were then processed by Pearson Correlation Analysis using One Tailed. The results of the correlation analysis test are that (1) there is a negative relationship between self-efficacy and academic procrastination; (2) there is a negative relationship between time management and academic procrastination; and (3) there is a negative relationship between self-motivation and academic procrastination.